Magnetic resonance fingerprinting review part 2: Technique and directions - McGivney, Debra F.; Boyacıoğlu, Rasim; Jiang, Yun; Poorman, Megan E.; Seiberlich, Nicole; Gulani, Vikas; Keenan, Kathryn E.; Griswold, Mark A.; Ma, Dan (Journal of magnetic resonance imaging, 2020)
Magnetic resonance fingerprinting (MRF) is a general framework to quantify multiple MR‐sensitive tissue properties with a single acquisition. There have been numerous advances in MRF in the years since its inception. In this work we highlight some of the recent technical developments in MRF, focusing on sequence optimization, modifications for reconstruction and pattern matching, new methods for partial volume analysis, and applications of machine and deep learning. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2020;51:993–1007.